The selector of souls : a novel - Baldwin, Shauna Singh (Toronto : Vintage Canada, 2013)
Two fascinating, strong-willed women must deal with the relentless logic forced upon them by survival: Damini, a Hindu midwife, and Anu, who flees an abusive marriage for the sanctuary of the Catholic church. When Sister Anu comes to Damini's home village to open a clinic, their paths cross, and each are certain they are doing what's best for women. What do health, justice, education and equality mean for women when India is marching toward prosperity, growth and becoming a nuclear power? If the baby girls and women around them are to survive, Damini and Anu must find creative ways to break with tradition and help this community change from within.
Keywords: Motherhood -- Fiction; India -- Social conditions -- Fiction